2022
DOI: 10.1021/jacs.1c12414
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecular Design to Enhance the Coherence Time of Quintet Multiexcitons Generated by Singlet Fission in Single Crystals

Abstract: Multiexciton quintet states, 5 (TT), photogenerated in organic semiconductors using singlet fission (SF), consist of four quantum entangled spins, promising to enable new applications in quantum information science. However, the factors that determine the spin coherence of these states remain underexplored. Here, we engineer the packing of tetracene molecules within single crystals of 5,12-bis(tricyclohexylsilylethynyl)tetracene (TCHS−tetracene) to demonstrate a 5 (TT) state that exhibits promising spin qubit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 78 publications
7
87
2
Order By: Relevance
“…In the second quantum revolution, we explore the unique spin degree of freedom of SF for quantum technologies 17,18 . It has been revealed that the | TT ⟩ spin sublevel with a magnetic quantum number ms = 0 can be selectively populated among five quintet sublevels because the state immediately after photoexcitation is a spinless singlet state, and the transitions occur by preserving its total spin [13][14][15][16] .…”
Section: (Tt)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second quantum revolution, we explore the unique spin degree of freedom of SF for quantum technologies 17,18 . It has been revealed that the | TT ⟩ spin sublevel with a magnetic quantum number ms = 0 can be selectively populated among five quintet sublevels because the state immediately after photoexcitation is a spinless singlet state, and the transitions occur by preserving its total spin [13][14][15][16] .…”
Section: (Tt)mentioning
confidence: 99%
“…To date, the spin aspect of SF has only been used to explain the microscopic mechanisms of SF. Because organic spin materials have advantages with their extremely small size, down to nanometers, and excellent bio-compatibility, it is worthwhile to research applications of the unique quintet state in quantum information science (QIS) and quantum biotechnologies 17,18 . Dynamic nuclear polarization (DNP) of biomolecules is one of the fields where polarized electron spins can play a pivotal role [19][20][21][22][23][24][25][26] .…”
Section: (Tt)mentioning
confidence: 99%
“…[6][7] Consequently, over the past several years, many experimental and theoretical investigations have been conducted to uncover new SF materials. [8][9][10][11][12][13][14][15][16][17][18][19][20] [21] To achieve the proper exergonicity for efficient SF, the singletexcited state energy level (ES, Fig. 1) of a substance must be higher than twice the energy level of its triplet-excited state (ET) (i.e., ES > 2ET).…”
Section: S1 + S0 ® [Tt] ® T1 + T1mentioning
confidence: 99%
“…However, recent spectroscopic studies have revealed that the triplet-pair undergoes spin dynamics, forming triplet 3 (TT) and quintet 5 (TT) multiexcitons [20,21], before dissociating into uncorrelated triplet excitons. High-spin states such as quintets have fundamental implications for the use of SF in photovoltaics [21], and have also been considered for quantum information processing applications [22]; understanding how these high-spin states form in SF, and how material design can affect their formation, presents an important unanswered question in the field [22].…”
Section: Introductionmentioning
confidence: 99%